The influences of gender, generation, and racial/ethnic groups on adaptations to hegemony in contemporary America - Burrell, Jah-rael Victor (Kansas State University, 2009)
The purpose of this study is to examine the affects of hegemonic influences on race and ethnicity among American families. An underlying premise of the investigation is that intra-familial socialization (what one is taught at home) and how external interaction (i.e., social environment) affects the perceptions of racial, ethnic American identity. That is, how does what is taught at home and what is absorbed in our social environments influence how we feel about being American. An overlay of generational effects, race, and gender are examined. Data were extracted from the National Opinion Research Center, General Social Surveys (GSS), for the year 2004. The final sub-sample used for this investigation consisted of approximately 1300 adults. Using theoretical constructs from generational effects, social exchange, and social integrationist approaches, an effort was made to identify what factors had the most influences on how families respond to hegemonic influence when group membership is controlled for in a series of correlations, Exploratory Factor Analyses, and Structure Equation Models (SEM) using Analysis of Moment Structures (AMOS). The results revealed that there were differences associated within and among generation, and racial/ ethnic populations, and gender.
Keywords: Hegemony; Race; Gender; Ethnicity; Generation Theory; Structural Equation Modeling; Psychology, Social (0451); Sociology, Ethnic and Racial Studies (0631); Sociology, Individual and Family Studies (0628)